1997
DOI: 10.1148/radiology.202.1.8988191
|View full text |Cite
|
Sign up to set email alerts
|

Infarctlike lesions in the brain: prevalence and anatomic characteristics at MR imaging of the elderly--data from the Cardiovascular Health Study.

Abstract: If the lesions reported in this study indicate cerebrovascular disease, subclinical disease may be more prevalent than clinical disease, and the prevalence of disease may rise with age. Also, infarctlike lesions have a distinctive anatomic profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
128
2
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(135 citation statements)
references
References 0 publications
2
128
2
3
Order By: Relevance
“…That these associations were relatively weak and inconsistent, particularly after adjusting for IMT/stenosis, does not lend support for a direct pathogenic mechanism. Limiting analyses to large or watershed infarcts, which are more likely to be due to large-vessel atherosclerosis than to small-vessel hypertensive disease, 2,36 did not increase the strength of relationships with carotid plaque characteristics and thus also fails to support a direct pathogenic role for carotid disease. Conversely, the strong and consistent associations of small infarct-like lesions with plaque heterogeneity, especially given the lack of association of these lesions with carotid atherosclerosis severity and many other cardiovascular disease risk factors, raises questions about the pathogenesis of these mysterious lesions that may merit further investigation.…”
Section: Manolio Et Al February 1999 361mentioning
confidence: 81%
See 3 more Smart Citations
“…That these associations were relatively weak and inconsistent, particularly after adjusting for IMT/stenosis, does not lend support for a direct pathogenic mechanism. Limiting analyses to large or watershed infarcts, which are more likely to be due to large-vessel atherosclerosis than to small-vessel hypertensive disease, 2,36 did not increase the strength of relationships with carotid plaque characteristics and thus also fails to support a direct pathogenic role for carotid disease. Conversely, the strong and consistent associations of small infarct-like lesions with plaque heterogeneity, especially given the lack of association of these lesions with carotid atherosclerosis severity and many other cardiovascular disease risk factors, raises questions about the pathogenesis of these mysterious lesions that may merit further investigation.…”
Section: Manolio Et Al February 1999 361mentioning
confidence: 81%
“…2 Given the strong and consistent relationships of MRI abnormalities to severity of carotid atherosclerosis, the question arises whether there are other ultrasound-definable characteristics of carotid disease that are related to MRI abnormalities. Clinical studies of carotid atherectomy specimens suggest that ulcerated, 20 less organized, 15 and hemorrhagic 21,22 plaques are associated with symptoms.…”
Section: Carotid Disease and The Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…While numerous reports have documented the frequency of presumed infarctions on CT or MRI in persons with a history of (or at risk for) overt stroke [8]- [12], few studies have reported prevalence of such lesions in an asymptomatic community-dwelling population [13].…”
Section: Discussionmentioning
confidence: 99%